(untitled) (Zaporizhzhia Historical Review, 2021)
The author describes peculiarities of personnel policies of USSR government during 1917-1919 at the Ukraine’s territory. He proves the major aim of the policy was strengthening Central Committee of Soviet Communist Party (Bolshevik) power in Ukraine. Variations in appointing the leaders in Soviet Ukraine were caused by tactical calculations only, subdued to the main goal.